Development and usability evaluation of a user-centred diet management informatics module for parents of children with leukaemia - Dong, Xiaolan (My University, 2023)
Leukaemia is the most common childhood cancer, with a five-year survival rate of 90% in children under 14. The children with leukaemia faced challenges in dietary management, including their insufficient knowledge about dietary management, passive acceptance of dietary restrictions, lack of participation behaviour, and poor experience in dietary management. This study aimed to identify the content and functional requirements of the diet management module as perceived by parents of children with leukaemia, following the agile development method to develop a user-centred diet management module accordingly and evaluate its usability. The “user-centred” design approach was adhered to in this study, employing a content analysis method and one-on-one interviews to identify the needs of parents participating in the diet management of children with leukaemia. Based on the needs, a draft of the dietary knowledge base was developed, further refined through expert review to construct the image-text knowledge base. A multidisciplinary team was formed to conduct brainstorming for the conceptual design of the module's user interface (UI) and to determine the detailed functional design, followed by module construction. During the development phase, formative usability evaluations were conducted to assess the UI and functionality, and optimization measures were implemented accordingly. Finally, a summative usability evaluation was conducted, combining typical task testing, mHealth APP Usability Questionnaire (MAUQ) for Interactive mHealth APPs Used by Patients, and qualitative interviews. A formative usability evaluation method was employed in the agile development process of the diet management module, where a multidisciplinary research team of 9 members evaluated and improved the UI design and module functionality. The summative usability evaluation method was used to evaluate the usability of the diet management module, which involved 20 parents of children with leukaemia, six healthcare providers from a Haematology-Oncology department at the tertiary children’s hospital in Shanghai, and a combination of typical task testing, mHealth APP Usability Questionnaire (MAUQ) for Interactive mHealth APPs Used by Patients, and qualitative interviews. To address the need for parental support in managing the diet of children with leukaemia, an image-text knowledge base comprising 105 articles was constructed, comprising the following categories: Recipes for children under one year old, two to three years old, over four years old, and eating guidelines. The module encompassed several functions, including information actively browsing and searching function, diet recommendations based on different treatment phases, diet recommendations based on the patient’s age group, content-based dietary recommendations, and menu recommendations. The overall MAUQ score was 2.15 (scores range from 1 to 7, with results closer to 1 indicating higher usability). The three dimension scores were as follows: usability and satisfaction (1.92), system information arrangement (2.13), and efficiency (2.44). The usability testing results indicated that the module had good overall usability. In conclusion, the research findings demonstrated that the module exhibited good usability. It potentially meets the diet management support needs of parents in future efficacy evaluations, alleviates the burden of diet management for parents, and enhances the effectiveness of diet management for children with leukaemia.

Leukemia on yleisin lapsuusiän syöpä, jonka viiden vuoden eloonjäämisaste on 90 prosenttia alle 14-vuotiailla lapsilla. Leukemiaa sairastavilla lapsilla on haasteita ruokavalion hallinnassa johtuen muun muassa riittämättömistä tiedoista sekä puutteellisesta ruokavaliohoitoon sitoutumisesta ja ruokavaliohoitoon osallistumisesta. Tässä tutkimuksessa pyrittiin tunnistamaan ruokavalionhallintamoduulin sisältö ja toiminnalliset vaatimukset leukemiaa sairastavien lasten vanhempien näkemyksen mukaan, kehittämään käyttäjäkeskeinen ruokavalionhallintamoduuli ja arvioimaan sen käytettävyyttä. Tässä tutkimuksessa noudatettiin "käyttäjäkeskeistä" suunnittelutapaa, jossa käytettiin sisällönanalyysimenetelmää ja ruokavalion hallintaan osallistuvien vanhempien henkilökohtaisia haastatteluja vanhempien tarpeiden tunnistamiseksi. Tarpeiden perusteella laadittiin luonnos ravitsemustietokannasta, jota jalostettiin edelleen asiantuntijakatsauksen avulla kuva-tekstitietopohjan rakentamiseksi. Moduulin käyttöliittymän (UI) käsitteellistä suunnittelua varten muodostettiin monialainen tiimi (n=9), jonka tehtävänä oli määrittää yksityiskohtainen toiminnallinen malli, jota seurasi moduulin rakentaminen. Kehitysvaiheessa tehtiin käytettävyysarviointeja käyttöliittymän ja toimivuuden arvioimiseksi ja optimointitoimenpiteitä toteutettiin niiden mukaisesti. Lopuksi suoritettiin käytettävyysarviointi, johon osallistui 20 leukemiaa sairastavan lapsen vanhempaa ja kuusi terveydenhuollon ammattilaista Shanghain lastentautien sairaalan hematologis-onkologiselta osastolta. Aineisto kerättiin moduulin testaamisen jälkeen kyselylomakkeella (mHealth APP Usability Questionnaire (MAUQ)) ja laadullisin haastatteluin. Vastatakseen vanhempien tuen tarpeeseen leukemiaa sairastavien lasten ruokavalion hallinnassa luotiin 105 artikkelista koostuva kuvatekstitietokanta, joka koostuu seuraavista luokista: Reseptit alle 1-vuotiaille, 2-3-vuotiaille, yli 4-vuotiaille lapsille ja syömisohjeet. Moduuli sisälsi useita toimintoja, kuten tiedon aktiivisen selaus- ja hakutoiminnon, eri hoitovaiheisiin perustuvat ruokavaliosuositukset, potilaan ikäryhmään perustuvat ruokavaliosuositukset, sisältöön perustuvat ruokavaliosuositukset ja ruokalistasuositukset. MAUQ:n yleisin pistemäärä oli 2,15 (pisteet vaihtelevat 1–7 välillä, ja tulokset lähempänä yhtä osoittavat parempaa käytettävyyttä). Kolmen ulottuvuuden pisteet olivat seuraavat: käytettävyys ja tyytyväisyys (1,92), järjestelmätietojen sommittelu (2,13) ja tehokkuus (2,44). Käytettävyystestauksen tulokset osoittivat, että moduulin kokonaiskäytettävyys oli hyvä. Yhteenvetona voidaan todeta, että tutkimustulokset osoittivat, että moduulin käytettävyys oli hyvä. Se vastaa potentiaalisesti vanhempien ruokavalionhallinnan tukitarpeita tulevissa tehokkuusarvioinneissa, keventää vanhempien ruokavalion hallinnan taakkaa ja kasvattaa tehokkuutta leukaemiaa sairastavien lasten ruokavalion hallinnassa.
Keywords: mHealth, Leukaemia, Diet Management, Diet Recommendation, Usability Evaluation